Physical Exercise with Music Reduces Gray and White Matter Loss in the Frontal Cortex of Elderly People: The Mihama-Kiho Scan Project - Tabei, Ken-ichi; Satoh, Masayuki; Ogawa, Jun-ichi; Tokita, Tomoko; Nakaguchi, Noriko; Nakao, Koji; Kida, Hirotaka; Tomimoto, Hidekazu (Frontiers in Aging Neuroscience, 2017)
Findings from previous studies suggest that physical exercise combined with cognitive training produces more positive effects on cognitive function in elderly people than physical exercise alone. However, the brain plasticity associated with these proposed benefits of combined therapy has not yet been investigated in elderly subjects. We hypothesized that the dual task group would experience greater benefits than the physical exercise alone and non-exercise control groups with regard to both cognitive function and brain plasticity. This study investigated the effect of physical exercise with musical accompaniment on structural brain changes in healthy elderly people. Fifty-one participants performed physical exercise (once a week for an hour with professional trainers) with musical accompaniment (ExM), 61 participants performed the same exercise without music (Ex), and 32 participants made up the non-exercise group (Cont). After the 1-year intervention, visuospatial functioning of the ExM but not the Ex group was significantly better than that of the Cont group. Voxel-based morphometry analyses revealed that the ExM group showed greater right superior frontal gyrus volume and preserved volumes of the right anterior cingulate gyrus, left superior temporal gyrus, and insula. These results indicate that compared with exercise alone, physical exercise with music induces greater positive effects on cognitive function and leads to subtle neuroanatomical changes in the brains of elderly people. Therefore, physical exercise with music may be a beneficial intervention to delay age-related cognitive decline.